Performance analysis of convolutional code over different code rates and constraint length in wireless communication - Dhaliwal, Semardeep; Singh, Navdeep; Kaur, Gagandeep (2017 International Conference on I-SMAC (IoT in Social, Mobile, Analytics and Cloud) (I-SMAC), 2017)
The Forward Error Correction (FEC) is appropriate technique used for controlling error in modern data transmission over noisy communication channels. Convolutional coding using Viterbi decoding is one of the FEC technique used in modern wireless communication system. This paper analysis the bit error rate (BER) performance of Convolutional code over different Code rates and Constraint length using hard-decision Viterbi decoder. In this paper different Code rates 1/4, 1/3, 1/2, 2/3 and Constraint length from 3 to 8 are have been simulated using MATLAB over AWGN channel and QPSK modulation.